FROM STUDENTS TO ENTREPRENEURS: INTENTION DEVELOPMENT MODEL OF BECOMING ENTREPRENEUR AMONG STUDENTS - Delya Saski Ananda; Heri Yanto; Kusmuriyanto (Journal of Economic Education, 2026)
In the era of globalization and rapid technological development, entrepreneurship has become an important pillar in a dynamic economy. This research aims to explore the theory of planned behavior to explain the factors that influence the intention to become an entrepreneur. The population in this study were students at the Faculty of Economics, Universitas Negeri Semarang. The sampling technique uses a purposive sampling technique, namely students who have taken entrepreneurship courses as the criteria. The total research sample was 250 respondents.  The analysis technique in this research uses path analysis with the help of the AMOS 26 analysis tool. The research results show that the intention to become an entrepreneur among FEB UNNES students is influenced by student engagement in entrepreneurship courses, perceived behavioral control, attitudes and subjective norms. In addition, attitude variables can be influenced by perceived behavioral control and subjective norms. The suggestion in this research is that students can actively participate in entrepreneurial organizations on campus to gain experience and relationships so that they can create a supportive environment to become entrepreneurs or entrepreneurs.